Posterior reversible encephalopathy syndrome (PRES) in mesenteric leiomyosarcoma: A case report. (2018) - Schoucair, Ramy; Nicolas, Gregory; Ahdab, Rechdi; Bejjani, Noha; Abdalla, Eddie K.
Highlights: Posterior reversible encephalopathy syndrome, syndrome characterized by headache, confusion, visual loss and seizures. Mesenteric leiomyosarcoma causing Posterior reversible encephalopathy syndrome. Symptoms disappearance after resection of the tumor, suggests a renin production cessation. Abstract: Background: Posterior reversible encephalopathy syndrome (PRES) is a syndrome characterized by headache, confusion, visual loss and seizures. Many factors influence the appearance of this syndrome, predominantly eclampsia, certain medical treatments and malignant hypertension. Diagnosed by typical transient lesions on magnetic resonance imaging. Case Report: We present a case of mesenteric leiomyosarcoma in a 52 year old woman, who had severe headache, abdominal heaviness, and hypertension. Investigations revealed a mesenteric mass and aP osteriorR eversibleE ncephalopathyS yndrome features on brain MRI, suggesting renin secretion by the tumor, causing the patient's symptoms. Conclusion: Patient's symptoms disappeared after resection of the tumor, suggesting a renin production cessation.